2006
DOI: 10.1182/blood-2006-03-007567
|View full text |Cite
|
Sign up to set email alerts
|

Association of a novel regulatory polymorphism (−938C>A) in the BCL2 gene promoter with disease progression and survival in chronic lymphocytic leukemia

Abstract: Bcl-2 plays a key role in the regulation of apoptosis. We investigated the role of a novel regulatory single-nucleotide polymorphism (؊938C>A) in the inhibitory P2 BCL2 promoter in B-cell chronic lymphocytic leukemia (B-CLL

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
93
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 33 publications
9
93
4
Order By: Relevance
“…Also contrary to the study by Nuckel et al, 26 we did not find any significant difference in the length of the progression-free interval as indicated by time from diagnosis to the first treatment in our CLL cohort. Moreover, there was no indication that the BCL-2 polymorphism affects disease progression in CLL patients within any specific Binet stage or within mutated/unmutated subgroups.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Also contrary to the study by Nuckel et al, 26 we did not find any significant difference in the length of the progression-free interval as indicated by time from diagnosis to the first treatment in our CLL cohort. Moreover, there was no indication that the BCL-2 polymorphism affects disease progression in CLL patients within any specific Binet stage or within mutated/unmutated subgroups.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that our study cohort consists of a higher proportion of Binet stage B and C cases and cases carrying unmutated IGHV rearrangements. Thus, our cohort seems to have more aggressive clinical course than in the study by Nuckel et al 26 That notwithstanding, similar findings were observed when only stage A and mutated cases were analyzed. Furthermore, when the BCL-2 genotype status was combined with IGHV mutation data, no significant difference in overall survival was evident within either the IGHV-mutated or unmutated subgroups.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations